Failure analysis of a continuous press component in MDF production plant. (December 2017) - Lanzutti, A.; Andreatta, F.; Raffaelli, A.; Magnan, M.; Zuliani, L.; Fantoni, M.; Fedrizzi, L.
Abstract: This work presents the results of a failure analysis performed on a component of a continuous press that is a part of a process plant used to produce MDF (Medium Density Fibreboard) panels. This plant is composed of 2 counter rotating belts that are supported, internally, by small steel rollers, connected to each other by small axes. The failure occurred prematurely on rollers. These components undergo to static and dynamic stresses below the yield strength of material. Low alloyed steel is employed for the production of the rollers and the components are carburized on the external surface. The rollers present cracks on the external surface, that is in contact with the wood panels, already after few hours in service. Other components did not undergo cracking even for very long service times (about 5000 h). Both rollers that failed in service and rollers without cracks were characterized by optical and scanning electron microscopy in order to evaluate the microstructure of the components. In particular, the microstructure of the rollers was investigated on the surface and in the core of the rollers. Vickers micro-hardness measurements were employed for the characterization of the mechanical properties of the rollers. Successively, a cross section of a broken roller was characterized by scanning electron microscopy (SEM) On the same sample, after microstructural characterization, a micro-hardness profile was acquired from external surface to the core in order to evaluate possible over carburizing or oxidation phenomena. The results obtained from both the microstructural and mechanical characterization of the failed rollers indicate that the possible causes of the in service failure are related to quenching cracks or fatigue. Highlights: The work has presented a failure analysis of a structural component of a continuous press used to produce MDF (Medium Density Fiberboard). Surface hardened components are involved in the malfunction of the continuous press. The failed components have presented problems of intergranular oxidation and lack of tempering process. The problems could be solved by the use an alternative material or by a better control of treatment process.